2017
DOI: 10.1016/j.nano.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Systemic delivery of the tumor necrosis factor gene to tumors by a novel dual DNA-nanocomplex in a nanoparticle system

Abstract: Many cancers fail to respond to immunotherapy as a result of immune suppression by the tumor microenvironment. The exogenous expression of immune cytokines to reprogram the tumor microenvironment represents an approach to circumvent this suppression. The present studies describe the development of a novel dual nanoparticle (DNP) system for driving DNA expression vectors encoding inflammatory cytokines in tumor cells. The DNP system consists of a DNA expression vector-cationic nanocomplex (NC) surrounded by a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…New perspectives concerning intervention seem possible, and the use of nanotechnology could be a powerful approach to the use of cytokines in the prevention and treatment of cancer [ 302 304 ]. A better understanding of the relationship between inflammation and myeloma will ensure more effective therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…New perspectives concerning intervention seem possible, and the use of nanotechnology could be a powerful approach to the use of cytokines in the prevention and treatment of cancer [ 302 304 ]. A better understanding of the relationship between inflammation and myeloma will ensure more effective therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The DNP system was consisted of a DNA expression vector–cationic peptide nanocomplex (NC) surrounded by a PEG–PLA nanoparticle. The results showed that the DNP system could effectively induce apoptosis of tumor cells and possess highly anti-tumor efficacy in vivo (Shukla et al, 2017 ).…”
Section: Genementioning
confidence: 99%
“…Transfecting tumor cells to express these cytokines would be another way to achieve this effect locally [4446]. For example, a cationic polypeptide was used in one study to form nanocomplexes with plasmid DNA encoding tumor necrosis factor alpha (TNF-α) [47]. These nanocomplexes could be delivered either intratumorally or systemically and led to dramatically slower tumor growth in a breast tumor model.…”
Section: Therapeutic Immunoengineeringmentioning
confidence: 99%